2010
DOI: 10.1371/journal.pone.0008579
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Expression Is Regulated by Epigenetic Mechanisms in Prostate Cancer of TRAMP Mice

Abstract: Nuclear factor-erythroid 2 p45-related factor 2 (Nrf2) is a transcription factor which regulates the expression of many cytoprotective genes. In the present study, we found that the expression of Nrf2 was suppressed in prostate tumor of the Transgenic Adenocarcinoma of Mouse Prostate (TRAMP) mice. Similarly, the expression of Nrf2 and the induction of NQO1 were also substantially suppressed in tumorigenic TRAMP C1 cells but not in non-tumorigenic TRAMP C3 cells. Examination of the promoter region of the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
207
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(229 citation statements)
references
References 38 publications
15
207
0
4
Order By: Relevance
“…We have also reported that there is a progressive loss of Nrf2 expression and Nrf2 downstream target antioxidative genes, such as NQO1, HO-1, GSTm1, GCLC, and UGT1a1, during prostate cancer progresses in transgenic adenocarcinoma of mouse prostate (TRAMP) mice (5,9,10). Hypermethylated CpGs in the promoter region of Nrf2 gene was further found in TRAMP prostate tumors and TRAMP-C1 cells (11). The enhanced Nrf2 CpG methylation during TRAMP prostate tumor progresses was associated with the attenuated expressions of Nrf2 and its target genes (12).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…We have also reported that there is a progressive loss of Nrf2 expression and Nrf2 downstream target antioxidative genes, such as NQO1, HO-1, GSTm1, GCLC, and UGT1a1, during prostate cancer progresses in transgenic adenocarcinoma of mouse prostate (TRAMP) mice (5,9,10). Hypermethylated CpGs in the promoter region of Nrf2 gene was further found in TRAMP prostate tumors and TRAMP-C1 cells (11). The enhanced Nrf2 CpG methylation during TRAMP prostate tumor progresses was associated with the attenuated expressions of Nrf2 and its target genes (12).…”
Section: Introductionmentioning
confidence: 85%
“…The genomic DNAs were extracted and subjected to bisulfite conversion carried out using 750 ng of genomic DNA and applying to EZ DNA Methylation Gold Kits (Zymo Research Corp., Orange, CA) following the manufacturer's instructions. The converted DNA was amplified by PCR-utilizing Platinum PCR SuperMix (Invitrogen, Grand Island, NY) with a set of specific primers, forward: 5′-AGT TAT GAA GTA GTA GTA AAA A-3′ and reverse: 5′-AAT ATA ATC TCA TAA AAC CCC AC-3′, amplifying the first five CpGs located between −1,266 and −1,086 of the promoter region of Nrf2 with the translation initiation site defined as +1 (11,14). Gel extraction using Qiaquick™ gel extraction kit (Qiagen, Valencia, CA) were used to purify the PCR products, then cloned into pCR4 TOPO vector using a TOPO™ TA Cloning kit (Invitrogen, Grand Island, NY).…”
Section: Dna Extraction and Bisulfite Genomic Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this leads to the expression of Nrf2 (Wang et al 2008;Muscarella et al 2011). Conversely, DNA methylation by DNA methyltransferases (DNMTs) appears to downregulate the Nrf2 expression indirectly (Khor et al 2014;Yu et al 2010;Rajabi et al 2016;Tagde et al 2016b). (c) Accumulation of p21 and p62 disrupts the Nrf2-Keap1 complex: it has been demonstrated that p53 negatively regulates Nrf2 and specifically suppresses the transcription of target genes of Nrf2 (Faraonio et al 2006).…”
Section: Role Of the Nrf2-keap1 Pathway In Cancermentioning
confidence: 99%
“…Nrf2 gene promoter methylation associated with methyl-CpG-binding protein 2 and histone modifications epigenetically down-regulated the expression of Nrf2 in murine tumor models. 99 Genetic disruption of molecular clocks alters the rhythmic activation of Nrf2 and potentiates fibrosis in a lung injury model. 35 Although age-related declines in circadian rhythms are known to occur, 100 it is not known whether changes in the expression of clock genes and altered circadian rhythms lead to increased susceptibility to age-related lung fibrosis through impaired activation of Nrf2.…”
Section: Keap1-independent Mechanismsmentioning
confidence: 99%